Patient satisfaction in inpatient psychiatric treatment compared with inpatient equivalent home treatment in Germany: an in-depth qualitative study - Adam, Nele; Neumann, Melanie; Edelhäuser, Friedrich (Frontiers in Health Services, 2023)
Background: Inpatient treatment (IT) is the predominant form of psychiatric care in Germany and internationally, whereby forms of psychiatric treatment have mainly evolved in the direction of home services. Inpatient equivalent home treatment (IEHT) is a new and additional pillar of psychi-atric acute care provision legally embedded since 2018 in Germany. Objective: The aim of this study is to conduct an in-depth exploration as little qualitative research has been done so far in Germany to examine possible differences in patient satisfaction with IT compared to IEHT. Methods: In the current qualitative study N=9 patients of a German hospital providing IT and IEHT were interviewed with the Problem-centered Interview. Inclusion criteria were IT or IT with subsequent IEHT. Participants’ experiences during their psychiatric treatment were analyzed by using Qualitative Content Analysis. Results: The results of both types of psychiatric treatment refer to different satisfaction fac-tors during the treatment period. The function of fellow patients, the setting of the treatment, condi-tions in place and the relationship to relatives turn out to be pivotal for patient satisfaction. Addi-tionally, the quality of the therapy and relationship to caregivers itself can have an impact on pa-tient satisfaction, particularly by shared decision making. During the IEHT, patient satisfaction can be strengthened by the possibility to handle daily tasks, to be close to relatives, while not so close to fellow patients, whereas in IT patients are mostly satisfied because of the distance to their every-day life and the closeness to fellow patients. The choice of the form of psychiatric treatment ac-cording to patients’ individual needs seems to be one key driver which can increase patient satisfaction. Additionally, a clean and hygienic environment seems to be critical for our respond-ents as a lack of it is one of the reasons leaving the treatment. Conclusions: Despite its limitations, this hypothesis-generating study is one of the first investigat-ing German IEHT in comparison to IT in an in-depth qualitative approach contributing to a patient-oriented and cost-effective psychiatric treatment. German and international providers of IEHT may derive several generic success factors from this study for the development and improvement of pa-tient satisfaction.